Job's illness : loss, grief, and integration : a psychological interpretation - Kahn, Jack H.; Solomon, Hester (Pergamon international library of science, technology, engineering, and social studies., 1975)
Job's Illness: Loss, Grief and Integration explores the Book of Job and examines the psychiatric interpretation of Job's illness. This book presents the story of Job to help the readers to discover the links between depression, obsessional states, and paranoia.